A CROSS-SECTIONAL STUDY ON PREOPERATIVE SURGICAL SITE HAIR REMOVAL FOR ELECTIVE ABDOMINAL SURGERY IN JHARKHAND, INDIA: DOES IT HAVE IMPACT ON SURGICAL SITE INFECTION? - Aftab Ahmed; Utkrisht Kant (Student’s Journal of Health Research Africa, 2024)
Background Hair removal at surgical sites, a common preoperative practice to prevent surgical site infections (SSIs) attributed to hair follicles, is often deemed hygienic. However, the literature indicates no significant correlation between hair removal and infection occurrence, making it a questionable ritual for infection prevention. Method This study was conducted prospectively at the surgery department of the Shaheed Nirmal Mahto Medical College & Hospital, Dhanbad. The abdominal surgeries conducted in a year were included in this study. Two groups were formed. The first group underwent removal of hair whereas the other group did not undergo the hair removal process. The occurrence of infection was thoroughly evaluated and the data obtained from both the groups were compared. The patients were evaluated during the 7th day, 14th day, and a month of the surgery Results In this study of 200 patients (138 males, 62 females) undergoing various surgeries (88 laparoscopic, 112 open), 21 developed surgical site infections (SSIs) during 7, 14, and 30-day follow-ups. Despite higher SSIs in the shaved group, differences in wound scores, pain, suture type, BMI, surgery type, gender, or anesthesia administration were not statistically significant. Clean contaminated surgeries and surgeries under 2 hours showed increased SSIs. Conclusion From this study, it is found that when the duration of the surgery is less than 2 hours and the surgery of the clean contaminated category then there is a statistically significant difference in the shaved and unshaved group considering the number of SSI. Otherwise shaving does not cause any alteration in the number of SSIs. Recommendation Shaving should be considered preoperatively if its potential benefits outweigh the occurrence of surgical site infection. Also in case of clean contaminated open surgeries, a rigorous prophylaxis of antibiotics should be given.